Taking First-Year Students to Court: Disorienting Moments As Catalysts for Change - Emily Hughes (Washington University Journal of Law & Policy, 2008)
This Essay explores the advantages and limitations of taking first-year criminal law students to court to provide a nontraditional first-year experience that encourages students to consider how power and privilege operate within the construction of criminal law. Taking students to court can be a deliberate attempt to disorient them, to encourage them to question the very moorings on which criminal law rests. While the concept of “disorienting moments” is extensively discussed in clinical literature, few scholars have discussed how this teaching tool might be used in a large doctrinal class. Creating “disorienting moments” for first-year criminal law students by taking them to court is an example of one such teaching tool.
Keywords: Criminal law – Study & amp; teaching; Clinical legal education; Social justice; Law students; Legal education; Teaching methods; United States